Color Transitions in Tanjung-2 Chili Pepper at Green and Red Harvest Stages under Varying Growing Structures and Fertigation Levels - Meivie Tivalli; Kusumiyati Kusumiyati; Shazma Anwar; Konain Zahra Maqbool; Md Shazzadul Islam (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Fruit color is a primary determinant of market acceptance for chili peppers (Capsicum annuum L.). This study quantified the green-to-red color transition at harvest using the CIELAB system. The experiment had a split-plot RCBD. Four growing structures as main plots: greenhouse, screen house, rain shelter, and open field. Four fertigation levels (25, 50, 75, and 100% ETc) as subplots. Color parameters L*, a*, b*, chroma, hue, and ΔE* were measured at both green and red harvest stages. Interactions between structure and fertigation level were significant for all color parameters. At the green stage, L* and b* values were highest in the screenhouse and greenhouse at 75–100% ETc. At the red stage, a* and chroma increased markedly, while hue decreased rapidly. This indicated accelerated carotenoid accumulation. Maximum ΔE* was observed in greenhouse and screenhouse with 100% ETc. Screenhouse with 75–100% ETc for the green harvest stage yields higher lightness (L*) and b* values. An open field combined with 50% ETc should be recommended for the red harvest phase to achieve higher a*, chroma, and ΔE* values, indicating improved red color intensity and visual quality. ΔE* was observed with 100% ETc, indicating accelerated ripening and a shorter harvest period.